Prognostic Role of Porphyromonas gingivalis Gingipain Rgp and Matrix Metalloproteinase 9 in Oropharyngeal Squamous Cell Carcinoma - Kylmä Anna Kaisa; Sorsa Timo; Jouhi Lauri; Mustonen Harri K; Mohamed Hesham; Randén-Brady Reija; Mäkitie Antti; Atula Timo; Hagström Jaana; Haglund Caj (International Institute of Anticancer Research, 2022)
BACKGROUND / AIM
The oral bacteria involved in the development of periodontitis alter the tissue conditions and modify immune responses in a way that may also influence tumor development. We investigated the prevalence of R gingipain (Rgp), a key virulence factor of the oral pathobiont Porphyromonas gingivalis, and the tissue-destructive enzymes matrix metalloproteinase 8 (MMP-8) and 9 (MMP-9) in 202 unselected consecutive oropharyngeal squamous cell carcinoma (OPSCC) samples. We further investigated the relationships between these factors and human papillomavirus (HPV) status, Treponema denticola chymotrypsin-like proteinase (Td-CTLP) immunoexpression, clinical parameters, and patient outcome.
PATIENTS AND METHODS
Clinicopathological data were derived from university hospital records. Rgp, MMP-8, and MMP-9 immunoexpression was evaluated by immunohistochemistry; the immunohistochemistry of Td-CTLP and HPV has been described earlier for this patient series. Cox regression analysis including death by causes other than OPSCC as a competing risk served to assess sub distribution hazard ratios.
RESULTS
In multivariable survival analysis, positive tumoral MMP-9 immunoexpression predicted poor prognosis among all patients [sub distribution hazard ratio (SHR)=2.4; confidence interval (CI)=1.2-4.4, p=0.008], and especially among those with HPV-negative OPSCC (SHR=3.5; CI=1.7-7.3, p=0.001). Positive immunoexpression of Rgp in inflammatory cells was associated with favorable outcome among all patients (SHR=0.5, CI=0.2-0.9, p=0.021) and among those with HPV-negative disease (SHR=0.4, CI=0.2-0.9, p=0.022).
CONCLUSION
Our results suggest that tumoral MMP-9 may be related to poor outcome in OPSCC, especially in HPV-negative disease, while Rgp immunoexpression in inflammatory cells is associated here with better disease-specific survival (DSS).